2010
DOI: 10.1200/jco.2009.25.7899
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate in Advanced Dermatofibrosarcoma Protuberans: Pooled Analysis of Two Phase II Clinical Trials

Abstract: Purpose Dermatofibrosarcoma protuberans (DFSP) is a dermal sarcoma typically carrying a translocation between chromosomes 17 and 22 that generates functional platelet-derived growth factor B (PDGFB). Patients and Methods Two distinct phase II trials of imatinib (400 to 800 mg daily) in patients with locally advanced or metastatic DFSP were conducted and closed prematurely, one in Europe (European Organisation for Research and Treatment of Cancer [EORTC]) with 14-week progression-free rate as the primary end po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
181
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 337 publications
(193 citation statements)
references
References 54 publications
6
181
0
6
Order By: Relevance
“…10,11 In recent years, however, the insight has emerged that systemic therapy should become more tailored, and particularly for STS, according to histologic subtype. This approach is illustrated clearly by the relevant activity of imatinib in advanced dermatofibrosarcoma protuberans, 12,13 paclitaxel in angiosarcoma, 14,15 gemcitabine in leiomyosarcomas, 16,17 trabectedin in patients with myxoid/round cell liposarcomas, 18 and of mammalian target of rapamycin inhibitors in perivascular epithelioid cell tumors. 19 This evolution has been associated over the last 2 decades with the widespread use of additional lines of chemotherapy along with first-line anthracycline-based regimens; the increasing participation of patients with STS in investigational agents trials; the increased used of locoregional treatments for metastatic disease (surgery, radiofrequency ablation); and the general improvement in oncology supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In recent years, however, the insight has emerged that systemic therapy should become more tailored, and particularly for STS, according to histologic subtype. This approach is illustrated clearly by the relevant activity of imatinib in advanced dermatofibrosarcoma protuberans, 12,13 paclitaxel in angiosarcoma, 14,15 gemcitabine in leiomyosarcomas, 16,17 trabectedin in patients with myxoid/round cell liposarcomas, 18 and of mammalian target of rapamycin inhibitors in perivascular epithelioid cell tumors. 19 This evolution has been associated over the last 2 decades with the widespread use of additional lines of chemotherapy along with first-line anthracycline-based regimens; the increasing participation of patients with STS in investigational agents trials; the increased used of locoregional treatments for metastatic disease (surgery, radiofrequency ablation); and the general improvement in oncology supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Despite the large number of genomic mutations in soft-tissue sarcomas no other targeted treatment is eff ective and the role of anti-angiogenic treatment is unclear. [15][16][17] Three phase 2 studies have been done to test antiangiogenic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the role of IM in the metastatic setting is not clarified. Both the prospective and the retrospective studies reported so far analyzed locally advanced and metastatic patients together, and the efficacy of IM treatment was not investigated specifically in FS-DFSP (11)(12)(13)(14)(15). We already reported on 4 patients with advanced, translocated FS-DFSP (3 metastatic, one locally advanced) who received IM (5).…”
Section: Introductionmentioning
confidence: 99%